2004
DOI: 10.1016/j.thbio.2004.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The duplication of the Hox gene clusters in teleost fishes*1

Abstract: Higher teleost fishes, including zebrafish and fugu, have duplicated their Hox genes relative to the gene inventory of other gnathostome lineages. The most widely accepted theory contends that the duplicate Hox clusters orginated synchronously during a single genome duplication event in the early history of ray-finned fishes. In this contribution we collect and re-evaluate all publicly available sequence information. In particular, we show that the short Hox gene fragments from published PCR surveys of the kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 72 publications
2
28
0
Order By: Relevance
“…The identities of the PCR fragments were also investigated by reconstructing phylogenetic trees using different methods following the procedure outlined by Prohaska and Stadler (2004). Neighbor-joining (Saitou and Nei,'87), parsimony, and maximum likelihood analysis for each PG was performed using the Phylip package (Felsenstein,'89), using other teleost Hox homeobox fragments for comparison (D. rerio, Tetraodon nigroviridis, Takifugu rubripes, Oryzias latipes, and Fundulus heteroclitus).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The identities of the PCR fragments were also investigated by reconstructing phylogenetic trees using different methods following the procedure outlined by Prohaska and Stadler (2004). Neighbor-joining (Saitou and Nei,'87), parsimony, and maximum likelihood analysis for each PG was performed using the Phylip package (Felsenstein,'89), using other teleost Hox homeobox fragments for comparison (D. rerio, Tetraodon nigroviridis, Takifugu rubripes, Oryzias latipes, and Fundulus heteroclitus).…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, questions such as the characterization of evolutionary patterns after the FSGD including Hox gene retention/deletion, and evolution at the nucleotide level is of particular interest (Holland et al, '94;Malaga-Trillo and Meyer, 2001;Wagner et al, 2003;Prohaska and Stadler, 2004;Hoegg and Meyer, 2005;Crow et al, 2006;Kurosawa et al, 2006). Available DNA sequences from teleosts have shown a variety of gene retention and deletion patterns.…”
mentioning
confidence: 99%
“…After identifying many supernumerous Hox genes to the already known ones from tetrapods (Njolstad et al, 1988;Misof and Wagner, 1996;Aparicio et al, 1997), the 5 systematic evaluations of Hox genes revealed seven Hox clusters in zebrafish (Amores et al, 1998;Prince et al, 1998) as opposed to the four found in tetrapods. Although duplicated Hox genes have also been identified in other teleosts, it was initially not clear whether the increase in the number of Hox clusters is universal for teleosts (Prohaska and Stadler, 2004). Recently, duplicated Hox gene clusters were found in the two most basal extant groups of teleost fishes, the Elopomorpha (including eels and tarpons) (Guo et al, 2009;Henkel et al, 2012).…”
Section: Wgds Have Shaped Teleost Evolution a Wgd Took Place In The Cmentioning
confidence: 99%
“…Some have argued for a direct causal linkage such that genome duplication drives a geologically instantaneous burst of evolution (Sidow 1996;Wagner et al 2003), while others have argued for a more permissive role wherein genome duplication is a necessary prerequisite of organismal evolution, but the effect on organismal evolution unfolds gradually over a protracted period of time (Prohaska and Stadler 2004). The principal evidence marshaled in support of the evolutionary burst hypothesis is the observation that living vertebrates and gnathostomes are distinguished from living invertebrate chordates and jawless vertebrates, respectively, by very large inventories of anatomical and developmental characters-surely only genome duplication can explain the emergence of so many characters in concert?…”
Section: Genetic Drivers Of Vertebrate and Gnathostome Innovationmentioning
confidence: 99%